The public accountant in the face of the fourth industrial revolution - Gómez Méndez, Julio (2020)
Objective: Evidence of whether Public Accountants in Peru are trained to confront the fourth industrial revolution and analyze the professional competencies of accounting to provide services in digitized economic entities. Method: The research is qualitative, non-experimental documentary, so far as the variables have not been manipulated, but the phenomenon under study has been observed through the analysis, criticism and comparison from several sources of information, considering authenticity, credibility, representation and meaning. Results: The Industrial revolution 4.0 does not replace the public accountants but it does require new competences. Public Accountants are still not prepared to deal the challenges of the fourth industrial revolution. Conclusions: Public Accountants in Peru must be in constant holistic training, updated to the technological changes, with interdisciplinary training, with normative knowledge and soft skills development.